2021
DOI: 10.1002/chem.202005285
|View full text |Cite
|
Sign up to set email alerts
|

Spin–Orbit Charge‐Transfer Intersystem Crossing in Anthracene–Perylenebisimide Compact Electron Donor–Acceptor Dyads and Triads and Photochemical Dianion Formation

Abstract: Perylenebisimide (PBI)-anthracene (AN)d onor-acceptor dyads/triad were prepared to investigate spin-orbit charge-transfer intersystem crossing (SOCT-ISC). Molecular conformation was controlled by connecting PBI units to the 2-or 9-position of the AN moiety.S teady-state, time-resolved transient absorption ande mission spectroscopy revealed that chromophore orientation, electronic coupling, and dihedrala ngle between donor and acceptor exert as ignificant effect on the photophysical property.T he dyad PBI-9-AN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 114 publications
(197 reference statements)
3
36
0
Order By: Relevance
“…However, our recent studies show that the ESP is not strictly ISC mechanism-specific, that is, the triplet state formed via SOCT-ISC may show the same ESP as that formed by SO-ISC . We also found that the ESP of the triplet-state TREPR spectrum of a chromophore in the electron donor–acceptor dyads is not only dependent on the mutual orientation of the donor and acceptor, as proposed previously, it is also dependent on the structure of the electron donor (or acceptor) and even the number of the electron donors attached on the electron acceptor …”
Section: Resultssupporting
confidence: 76%
“…However, our recent studies show that the ESP is not strictly ISC mechanism-specific, that is, the triplet state formed via SOCT-ISC may show the same ESP as that formed by SO-ISC . We also found that the ESP of the triplet-state TREPR spectrum of a chromophore in the electron donor–acceptor dyads is not only dependent on the mutual orientation of the donor and acceptor, as proposed previously, it is also dependent on the structure of the electron donor (or acceptor) and even the number of the electron donors attached on the electron acceptor …”
Section: Resultssupporting
confidence: 76%
“…Although ISC was observed indirectly for the donor‐PDI dyads through 1 O 2 generation (Table 3), DFT optimized geometries indicated the absence of a perfect donor‐acceptor orthogonality (Table 1), often described as an essential feature in the SOCT‐ISC process [18] . However, recently reported PDI dyads showed the same deviation of the perpendicular donor‐acceptor orientation, while maintaining efficient SOCT‐ISC [9t,w] . To look deeper into the possible pathways for ISC, the quantum‐chemical and photophysical analyses were combined.…”
Section: Resultsmentioning
confidence: 99%
“…Barbon and coworkers developed carbazole‐PDI dyads with the carbazole donor attached to one of the two imide positions, [9t] while Fedin et al . chose to functionalize a bay‐position with a weakly donating anthracene moiety [9w] …”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the calculation of the vertical excitation energies, several effects that can significantly change the positions of the band maxima in the experimental spectrum were ignored. In particular, these calculations neglect the effects of vibrations (e.g., vibronic coupling and Jahn-Teller distortions) [45], spin-orbit coupling [46], and the environment [47], in cases where the spectra have been measured in solution or in a condensed medium. Hence, without including these additional effects in our calculations, there may be considerable discrepancies between the computed excitation energies and experimental band maxima, even with higher levels of theory and large basis sets.…”
Section: Atz Singlet Electronic Statesmentioning
confidence: 99%